PROSES PRODUKSI BERITA PADA MEDIA ONLINE DETIKCOM REGIONAL DETIKSULSEL (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2023)
Abstract: This research aims to: (1) Understand the stages of news production in the online media Detiksulsel, and (2) Understand the presentation of news in the online media Detiksulsel. This research uses a qualitative approach, with primary data sources namely chief editors, news editors, reporters and expert observers. Meanwhile, secondary data is various information obtained from books or references. Data collection methods are observation, interviews and documentation. The research instruments used cameras, notebooks, writing instruments, recording equipment and interview guides. Data analysis techniques use data reduction methods, data presentation and drawing conclusions. The results of this research show that (1) The Detiksulsel online media news production process goes through three stages, namely: a) Pre-production, at this stage the activities carried out are editorial meetings to determine news issues, search for information, and supporting data regarding related news coverage, b ) Production, at this stage the activities carried out by the reporter are collecting information and compiling the news script at the location of the incident quickly and precisely before editing by the news editor, c) Post-production, at this stage the editor is tasked with carrying out verification to see the accuracy and balance of news coverage. After checking and the news manuscript has been verified, the news editor uploads the news on the Detiksulsel website and social media. (2) Presentation of news on Detiksulsel online media, namely: a) Providing online media reporting channels, namely news, football, culture, tourism, culinary, business, South Sulawesi, law and crime. b) Applying the concept of real time news. The implications of this research recommend that Detiksulsel online media be able to realize its vision and mission so that the media's function as social control is realized as well as being a means of sharing knowledge for the sake of public intelligence as one of the functions of mass media. In the academic aspect, academics are expected to further develop competition and convergence of online media and print media. keywords: media production, news, mass media, online media